Implementasi Pembelajaran Terpadu Dalam Meningkatkan Kemampuan Literasi Siswa Madrasah Ibtidaiyah - Seventina Laily; Abu Dharin (J-PGMI: Jurnal Pendidikan Guru MI, 2024)
This research aims to analyze the implementation of integrated learning and literacy in MI Mafatihul Huda, an Islamic primary school in Serang, Cipari. The research method employed is a qualitative case study. Data were collected through observations, interviews, and document analysis. The findings indicate that integrated learning has been successfully incorporated by teachers, enhancing student engagement and improving their literacy skills. Teacher collaboration is seen as a key factor in the success of this implementation. This research contributes to the understanding of the importance of integrated learning and literacy in primary education in madrasahs.